Tapping the full potential of the digital revolution for agricultural extension: an emerging innovation agenda. Issue 5 (2nd November 2021) - Steinke, Jonathan; van Etten, Jacob; Müller, Anna; Ortiz-Crespo, Berta; van de Gevel, Jeske; Silvestri, Silvia; Priebe, Jan
ABSTRACT: Agricultural extension in the Global South can benefit greatly from the use of modern information and communication technologies (ICT). Yet, despite two decades of promising experiences, this potential is not fully realized. Here, we review the relevant research literature to inform future investments into agricultural information services that harness the full potential of digital media. We describe a recently emerging innovation agenda that is, in part, a response to the eventual failure of many new agro-advisory initiatives. One important cause of failure has been a focus on pushing certain technologies, rather than responding to the particular communication challenges of potential users. To avoid such bias in designing new services, the new innovation agenda rests on two major foundations: strong user-centredness and problem-orientation. In our review, we first describe how user-centred design methods help in specifying both problems and (digital) solutions in agricultural extension. To inform responses to the communication challenges defined by that analysis, we then describe eight emerging aspects of using ICT for development, and how they can address common deficiencies of agricultural extension. Practical examples from the literature highlight the possibilities and limitations of these innovation directions. Beyond digital design, however, technological innovation requires enabling institutions.